Hoax dan Misinformasi dalam Perspektif Islam sebagai Tantangan Nyata di Era Digital: Urgensi Tabayyun dan Literasi Digital Bagi Umat Muslim - Shofi Oktora Ramadhani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of information technology in the 21st century has fundamentally altered the ways in which humans communicate and access knowledge. While digital connectivity offers numerous benefits, it simultaneously fosters the unchecked proliferation of hoaxes and misinformation. This study aims to conduct a critical analysis of the false information phenomenon through the lens of Islamic jurisprudence and ethics. The research employs a qualitative method with a descriptive-analytical approach through library research, examining primary sources such as the Quran and Hadith, as well as secondary sources comprising scholarly journals, books, and institutional reports. The findings reveal that Islam maintains a firm and unambiguous prohibition against lying and disseminating false information. The concept of Tabayyun (verification) constitutes a methodological obligation incumbent upon every Muslim prior to believing or sharing any information. Spreading hoaxes is legally categorized as haram (forbidden) and falls within the category of major sins, as it encompasses elements of slander (fitnah), mendacity (kidzib), and harm (mafsadah). Islam views truth as the cornerstone of all virtue, while falsehood is the root of all corruption. Accordingly, digital literacy and religious literacy represent two essential pillars that Muslims must cultivate to navigate the challenges of modernity without transgressing Islamic norms.